Demoralization Effects of Sustainability: Development of a Theoretical Framework and Exploratory Pilot-Study on Moralization and Demoralization Effects in (M)Eating Behavior - Fenzl, Thomas; Weder, Franzisca; Voci, Denise; Lemke, Stella (Frontiers in Communication, 2022)
Sustainability is not only a moral compass for organizations of all kind and shape; increasingly it can be identified as social representation influencing social practices and behavior. Conceptually inspired by the idea of preferences, conventions, and moral convictions influencing individual behavior (Skitka et al., 2021) and an innovative concept of moral harmonization strategies (Weder, Tungarat & Lemke, 2020), this paper introduces a theoretical framework for the conceptualization of moralization effects in sustainability communication in general and food choices in particular. The framework is linked to empirical data from an exploratory qualitative pilot-study, in which we conducted guideline-based interviews with 25 international students to gather information on individual perceptions of food choices and eating behaviors. Interview data was analyzed using inductive category formation (Mayring & Fenzl, 2019) to explore what role sustainability plays on an individual level in terms of coming in as a value or norm and how much sustainability as a normative principle influences individual decision-making processes and behavior. Based on the results of the pilot-study, we hypothesize that food is less “morally overloaded” than expected and sustainability is not a moral imperative related to a specific eating behavior. In line with previous findings, our results confirmed that food choices and changes in meat consumption involve a multi-faceted and complex decision-making process, which among others may be heavily influenced by inherent social norms within a person’s social network, including family, friends as well as important other peers (Corallo et al., 2019; Zahra, McCarthy & Chaiechi, 2021). Thus, with this preliminary study, we critically challenge existing literature on the influence of sustainability as moral imperative guiding and influencing individual behavior, at least in the domain of food and eating behavior. To elaborate on our proposed framework, additional empirical research is needed from a cultural, sustainability, language, and communication perspective.